Panduan penggunaan program zoom-A berdasarkan strategi pembelajaran aktif - Baharom, Mohd. Munir (2014)
Zoom-A Programs has been widely used by primary schools throughout Malaysia after its launch in 2004. Although widely used, but its use is not maximums may cause dissatisfaction among parents. Although this program is getting good response from educators because it provides various facilities to help improve student achievement. This study was conducted to help serve as a guide for teachers to use the program at school. Through this study, the use of the Program Zoom A guide to active learning strategies have been developed. Three active learning strategy has been modified and used in accordance with the level and situation of students surveyed Number Head Together, Questions and Answers Common and Two Ten Strategies. The number of respondents involved is a total of 35 primary schools in the National School Kempas, Johor Bahru. A questionnaire was used as an instrument. The reliability of the instrument was a = 0908 indicates the instrument has high reliability. The data was analyzed using Statistical Package for Social Sciences (SPSS) 18.0 for frequency, percentage and mean. The results showed that the level of student achievement based on test content, Zoom Test A, the level of understanding and the advantages of using a zoom high level. T-test showed that the difference perception of these three activities and activities Ten Two strategies have the highest mean over all three. Some suggestions for improving the effectiveness of learning science to the pupils involved will demonstrate academic progress and improvement in using the Zoom A joint program of active learning activities